Changed frontal pole gene expression suggest altered interplay between neurotransmitter, developmental, and inflammatory pathways in schizophrenia - Scarr, Elizabeth; Udawela, Madhara; Dean, Brian (2018)
Schizophrenia (Sz) probably occurs after genetically susceptible individuals encounter a deleterious environmental factor that triggers epigenetic mechanisms to change CNS gene expression. To determine if omnibus changes in CNS gene expression are present in Sz, we compared mRNA levels in the frontal pole (Brodmann’s area (BA) 10), the dorsolateral prefrontal cortex (BA 9) and cingulate cortex (BA 33) from 15 subjects with Sz and 15 controls using the Affymetrix™ Human Exon 1.0 ST Array. Differences in mRNA levels (±≥20%; p < 0.01) were identified (JMP Genomics 5.1) and used to predict pathways and gene x gene interactions that would be affected by the changes in gene expression using Ingenuity Pathway Analysis. There was significant variation in mRNA levels with diagnoses for 566 genes in BA 10, 65 genes in BA 9 and 40 genes in BA 33. In Sz, there was an over-representation of genes with changed expression involved in inflammation and development in BA 10, cell morphology in BA 9 and amino acid metabolism and small molecule biochemistry in BA 33. Using 94 genes with altered levels of expression in BA 10 from subjects with Sz, it was possible to construct an interactome of proven direct gene x gene interactions that was enriched for genes in inflammatory, developmental, oestrogen, serotonergic, cholinergic and NRG1 regulated pathways. Our data shows complex, regionally specific changes in cortical gene expression in Sz that are predicted to affect homeostasis between biochemical pathways already proposed to be important in the pathophysiology of the disorder.